Bilateral malignant Brenner tumor of the ovary - Murat, Ayse; Ozdemir, Huseyin; Yildirim, Hanefi; Arslan, Anil; Ersoy, Ferda; Ozercan, Resat (My University, 2005)
Brenner tumors represent about 1.4% to 2.5% of ovarian tumors and are rarely malignant. Extensive amorphous calcification in a solid mass or solid component in a multilocular cystic mass is a characteristic finding of Brenner tumor of the ovary on CT and MRI. We present clinical, radiologic, and histologic findings of a 54-year-old female patient with bilateral malignant Brenner tumor of the ovary. Copyright © 2005 by Lippincott Williams & Wilkins.
Keywords: Brenner tumor; Computed tomography; Magnetic resonance imaging; Malignant; Ovary